KKN PEMBERDAYAAN MASYARAKAT MELALUI PENGUATAN LEMBAGA DESA DAN UMKM BERBASIS IPTEK DESA PANDANARUM - Rarasati, Ida Putri; Rohmatulloh, Gisca Bagus; Ilavi, Hawa Ayom; Athourrohman, Muhammad; Saputra, Prasetya Wisnu; Hariyanti, Rania Eka; Asyafa, Ridiyantoro (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
Real Work Lectures are the implementation of lectures in the form of community service. Students contribute and empathize with the conditions of society and are required to be able to solve existing problems. Activities carried out in Pandanarum hamlet, Pandanarum Village, Sutojayan District, Blitar Regency, use service methods in the form of counseling, socialization and group mentoring. The 2023 Real Work Lecture focuses on community empowerment, which is an effort to shape and prepare society towards continuous progress, independence, prosperity and social justice. The results obtained show a good level of success because they are in accordance with the level of active community participation, one of which was a positive response, including taking part in student socialization regarding stunting and digital marketing assistance for MSMEs through the village institution BUMDes Arum Jaya. Can obtain: (1) Increased knowledge of one of the village institutions in the form of knowledge to overcome stunting which is packaged in the RIAS (Innovation Revolution to Overcome Stunting) program; (2) Implementation of direct nutritional improvement through a free fishing program for communities, especially those classified as stunting data; (3) Real contribution in advancing the marketing of MSME products in Pandanarum Village through Shopee marketing.